Optimal machining parameters for micro-molds preparation - Quek, Mervyn Han Leng. (2011)
With the need for small parts in various industries such as the biomedical, aerospace and mechanical, the advancements in high speed machining will be a cost effective way to produce micro molds for injection molding. Micro molds are required to have high aspect ratios with great accuracy. It is also imperative that the machining parameters of this micro end milling process results in surface roughness of order less than a micron. Machining parameters such as spindle speed, feed rate, axial depth of cut and radial depth of cut will be varied on two materials, namely copper and stainless steel to find the most suitable set of values for each case. Using the design of experiments allowed us to perform a small number of experiments to achieve the optimal machining conditions so that it meets the manufacturing specification. The study done on burr formation will also allow for future projects to understand the effects of various machining parameters on the outcome of burr height formation. Some of the possible factors that have been found to affect burr formation are cutting speed, feed rate and possibly the tool wear characteristics. Since deburring is not a viable option in the micro-scale, this project will look into reducing burr formation through process controls rather than a separate post-process at the end. It is concluded in this report that despite the results achieved, it must be noted that the machining parameters are specific to this machine and the tool that was used.